2014
DOI: 10.1097/qai.0000000000000068
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Maternal HIV Testing and Uptake of Prevention of Mother-to-Child Transmission Interventions Among Women and Their Infected Infants in Johannesburg, South Africa

Abstract: Background By 2011, South African prevention of mother-to-child transmission of HIV (PMTCT) programmes had reduced perinatal HIV transmission at 6-weeks of age to 2.7%. We investigated the profile of newly-diagnosed vertically-infected children and their mothers to identify short-falls in the PMTCT programme. Methods In this operational follow-up study, fieldworkers enrolled mothers of newly-diagnosed HIV-infected children up to 2 years of age at 5 major healthcare facilities in Johannesburg. Structured ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 36 publications
7
29
2
Order By: Relevance
“…These women were eligible for ART but either did not engage in care or were not initiated on ART. In an analysis of PMTCT uptake among mothers in this cohort, we found that among women enrolled in PMTCT care only one in three meeting eligibility criteria were prescribed ART 34 . Barriers to ART initiation under Option A, the PMTCT approach at the time of this study, have been well described 35,36, 37 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These women were eligible for ART but either did not engage in care or were not initiated on ART. In an analysis of PMTCT uptake among mothers in this cohort, we found that among women enrolled in PMTCT care only one in three meeting eligibility criteria were prescribed ART 34 . Barriers to ART initiation under Option A, the PMTCT approach at the time of this study, have been well described 35,36, 37 .…”
Section: Discussionmentioning
confidence: 87%
“…The majority of children in our study were identified outside of PMTCT programs. We have previously shown that failure to diagnose HIV infection during pregnancy was a primary reason for missing both PMTCT and EID 34 . Furthermore, MTCT among women who acquire HIV during pregnancy also contributes disproportionately to new pediatric infections 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Rates of new infections are consistently higher in women (particularly those of reproductive age) than in men [2–4]. As a result of routine screening protocols, pregnancy is often the point at which an HIV diagnosis is made [5–7]. With intervention (preventing mother to child transmission, or PMTCT), the rate of vertical transmission of HIV is estimated at 1.4-5.9%, with an average of 3.5% [8].…”
Section: Introductionmentioning
confidence: 99%
“…Gaps identified in the PMTCT cascade that facilitate MTCT include late HIV diagnosis in pregnant women and subsequent lack of or delay in ART initiation during pregnancy. [13,19,20] These factors preclude the sufficient time on ART required to suppress maternal viraemia to levels protective against MTCT risk during pregnancy, at delivery, and during the postpartum period while breastfeeding. Additional potential PMTCT gaps include lack of virological suppression among women already on ART, inadequate prophylaxis for exposed infants, and discontinuation of care by mother-infant pairs (MIPs) postpartum.…”
Section: Researchmentioning
confidence: 99%